2023
DOI: 10.3389/fnut.2022.988529
|View full text |Cite
|
Sign up to set email alerts
|

Maternal prebiotic supplementation impacts colitis development in offspring mice

Abstract: Background and aimsMaternal diet plays a key role in preventing or contributing to the development of chronic diseases, such as obesity, allergy, and brain disorders. Supplementation of maternal diet with prebiotics has been shown to reduce the risk of food allergies and affect the intestinal permeability in offspring later in life. However, its role in modulating the development of other intestinal disorders, such as colitis, remains unknown. Therefore, we investigated the effects of prebiotic supplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…For example, Armstrong and colleagues found that unfermented inulin induced secretion of pro-inflammatory cytokines in a subset of IBD intestinal biopsies cultured ex vivo ( 150 ). In several other animal studies, researchers have found that dietary supplementation with inulin may be beneficial for low-grade inflammation and associated metabolic disease, but that it also exacerbates the severity of DSS-induced acute colitis ( 151 153 ). Furthermore, treatment with an “antibiotic cocktail” led to intestinal ecological dysregulation and induced colitis in mice, whereas supplementation with inulin-type fructans delayed the recovery of this antibiotic-induced intestinal inflammation and decreased the recovery of T reg and B cells in the lamina propria.…”
Section: Role Of Inulin In Diseasementioning
confidence: 99%
“…For example, Armstrong and colleagues found that unfermented inulin induced secretion of pro-inflammatory cytokines in a subset of IBD intestinal biopsies cultured ex vivo ( 150 ). In several other animal studies, researchers have found that dietary supplementation with inulin may be beneficial for low-grade inflammation and associated metabolic disease, but that it also exacerbates the severity of DSS-induced acute colitis ( 151 153 ). Furthermore, treatment with an “antibiotic cocktail” led to intestinal ecological dysregulation and induced colitis in mice, whereas supplementation with inulin-type fructans delayed the recovery of this antibiotic-induced intestinal inflammation and decreased the recovery of T reg and B cells in the lamina propria.…”
Section: Role Of Inulin In Diseasementioning
confidence: 99%